Students’ Attitudes towards Collaborative Learning through E-Learning During Covid-19: A Male and Female Students - Puspita Dewi; Abdul Muhid (English Teaching Journal : A Journal of English Literature, Language and Education, 2021)
The regulation and policy in the teaching and learning process are changing during this pandemic (Covid-19). The face-to-face learning process is altered by online learning. This evolution faces numerous obstacles throughout the world including in Indonesia. Information Communication and Technologies (ICTs) have a pivotal role in supporting materials and media for tutors or teachers in learning English because teachers can provide videos, music, and any other materials in e-learning that can be accessed everywhere and anytime by pupils. Collaborative learning could boost students’ motivation to learn English so that learning can be more interesting, easier, and interactive. The aims of this research are to identify students’ attitudes towards collaborative learning with ICTs through e-learning and to compare women's and men’s attitudes towards collaborative learning with ICTs through online learning. This research is mixed research namely quantitative research with a 5-point Likert scale using a questionnaire and qualitative by interviewing the students. The research results show that most of the students agree that collaborative learning through ICTs has a positive impact on learners’ attitudes during the pandemic. Then, females have a higher percentage than males in most of the items; however, males have much more interest in using the internet for their daily life. It is expected that government should provide some training to students not only on how to use the technology but also how to utilize the technology to gain appropriate materials; then blended learning would be much better to strengthen good communication and interaction between students and educators.